IMPLEMENTASI REKAM MEDIS ELEKTRONIK DI INSTITUSI PELAYANAN KESEHATAN DI INDONESIA - Ariyanto, Akhmad; Andriyanto, Arief (STIKES Insan Cendekia Medika Jombang, 2024)
ABSTRACT Electronic medical records as a manifestation of the transformation of the national health system in the field of technology are still considered a challenge. Based on Minister of Health Regulation no. 24 of 2022, it is stated that every health service facility in Indonesia is required to maintain electronic medical records. Unfortunately, the use of electronic medical records in Indonesian health service facilities is not yet fully distributed. The aim of this study is to look at the implementation of electronic medical records in health service facilities in Indonesia. This study was carried out using the literature review method using 8 journal articles obtained through Google Scholar and the Science and Technology Index (SINTA) with a publication time period of 2017-2022. The study results show that several health service facilities have implemented electronic medical records well, but some still have obstacles in implementing them. Through the results of this study, it is hoped that every health service facility can maximize the use of its electronic medical records to simplify health services.